Sward height management, desiccation time of Urochloa ruziziensis and nitrogen fertilization of soybean under crop-livestock system - Balbinot Junior, Alvadi Antonio; Franchini, Julio Cezar; Debiasi, Henrique (Revista de Ciências Agroveterinárias, 2016)
The integration of soybean crop with pastures is an important strategy to diversify the grain production systems in Brazil. The objective of this research was to evaluate the effect of grazing intensities in Urochloa ruziziensis, desiccation time of the pasture in relation to soybean sowing and crop fertilization with mineral nitrogen on the growth and yield of soybean, cultivar NK 7059 RR. Three grazing intensities of U. ruziziensis (15, 35 and 50 cm of plant height), were grazed continuously for six months, plus a no grazing paddock, making four experiments, were evaluated. In each experiment a randomized complete block design with three replications in a split plot design was used. In the plots were allocated four desiccation time of the pasture (35, 28, 20 and 8 days before soybean sowing) and in the subplots, nitrogen fertilization in soybean (without N or with 30 kg N ha-1 at sowing). Initially, analysis of each experiment was performed and subsequently a joint analysis was performed. The grazing intensities did not significantly affect the soybean growth and the yield. The increased interval between pasture desiccation and soybean seeding and the nitrogen fertilization on crop promoted increments in the growth and N accumulation by soybean in early development cycle. On the other hand, in the reproductive phase, these differences were negligible and did not affected the yield.